NAFKAH ISTRI YANG DI TALAK RAJ’I DALAM KEADAAN HAMIL - Fakhru Razik; Sitti Nurkhaerah; Desy Kristiane (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
Among the obligations of a husband, one of them is to provide a living for his wife and the obligation of a wife is to be obedient and obedient to her husband. The purpose of marriage will not be achieved if one of the parties neglects their obligations, this can create disputes in the family that result in divorce. The consequence of divorce for a wife, whether pregnant or not pregnant, is to undergo a period of iddah, either because of raj'i divorce or ba'in divorce. This study outlines several opinions, concepts or theories that describe or present problems related to the wife's right to earn a living from her ex-husband during the iddah period after being divorced from Raj'i in a pregnant state and the legal consequences for husbands who do not provide iddah. to the wife who was divorced while pregnant